Faktor-Faktor yang Memengaruhi Pengungkapan Emisi Karbon pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Witri Astiti, Ni Nengah; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 30 No 7 (2020), 2020)
Global warming is one of the environmental problems that causes climate change, especially related to corporate carbon emissions. This study aims to examine the factors that influence the disclosure of carbon emissions. This research was conducted on all companies listed on the Indonesia Stock Exchange that revealed information related to carbon emissions in the annual report in 2018. The sample in this research was selected purposively, producing samples with 37 companies. The data analysis technique in this research is multiple linear regression. The analysis shows that company the type of industry and good corporate governance has a positive effect, while leverage has a negative effect on disclosure of carbon emissions. Company size and profitability do no affect carbon emissions disclosure. Keywords: Global Warming; Climate Change; Carbon Emission Disclosures.